Exercise Prescription in Breast Cancer–Related Lymphedema: Safety, Functional Outcomes, and Practical Rehabilitation Strategies - Mohaissen, Rema; Tyla, Mikołaj; Stabrawa, Patryk; Więcko, Laura; Trela, Katarzyna; Tuteja, Aleksander; Warecki, Jakub; Słota, Jakub; Solarz, Kacper; Dylewicz, Łukasz (Quality in Sport, 2026)
Breast cancer-related lymphedema (BCRL) is a chronic complication of breast cancer treatment that may affect limb volume, symptoms, upper-limb function, activity and quality of life. Although limb avoidance was historically recommended, current evidence supports structured exercise in rehabilitation and survivorship care. This narrative review synthesized evidence on exercise prescription in BCRL, focusing on safety, resistance training, functional outcomes, compression, assessment and practical strategies.The strongest evidence concerns progressive resistance training. In selected patients with stable BCRL, gradual resistance training does not appear to worsen lymphedema outcomes with monitoring and precautions. In at-risk populations, resistance or multimodal exercise does not appear to increase BCRL risk, although prevention evidence remains mixed. Aerobic and mixed exercise may support fitness, fatigue, function and quality of life, but BCRL-specific dosing is less defined. Compression use varies across studies, supporting individualized decisions. Assessment should combine limb measures, symptoms, function, stage and patient-reported outcomes. Conclusions. Exercise should not be automatically contraindicated in patients with BCRL or women at risk. Prescription should consider baseline assessment, BCRL status, symptom stability, progressive loading, compression needs and monitoring. Future research should standardize definitions, compression protocols, exercise dosing, outcomes and event reporting.